A simple thin-layer chromatography autography for the detection of peroxidase inhibitors - Micheloni, Oscar Bernardo; Ramallo, Ivana Ayelen; Farroni, Abel Eduardo; Furlan, Ricardo Luis Eugenio (Springer Nature, 2024)
Thin layer chromatography bioautographic assays facilitate the acquisition of activity-profile chromatograms and assist in pinpointing active constituents within complex mixtures by observing the inhibition halos they produce. Peroxidase is an enzyme implicated in the browning of different fresh cut vegetables and in several diseases. A peroxidase bioautographic assay was developed, based on enzyme agarose immobilization and the 2,2′-Azino-bis(3-ethylbenzothiazoline-6-sulfonic acid) diammonium salt/radical cation (ABTS/ABTS·+) reporter system. Peroxidase was purified from potatoes with the aim to detect specific inhibitors. To reduce false positives, a non-enzymatic assay was also employed. The best results are obtained when a solution containing agarose, ABTS, hydrogen peroxide, and peroxidase in phosphate buffer is poured over the TLC plate (final concentrations: 0.031 mmoles/cm2, 0.239 µmoles/cm2, and 84.04 U/cm2) and incubated for 70 min. Limit of detection and quantification for quercetin is 0.16 µg and 0.54 µg, respectively. The developed system is able to detect quercetin in a Solidago chilensis Meyen extract and a peroxidase inhibitor in a Cichorium intybus L. extract. Therefore, the assay can detect inhibitory constituents in complex mixtures and differentiate between peroxidase inhibitors and ABTS·+ radical scavengers before any preparative fractionation, helping to take early operational decisions that can save time and resources.